Penghapusan Kriminalisasi Terhadap Hakim dan Jaksa dalam Rangka Mewujudkan Sinkronisasi Sistem Peradilan Pidana Anak - Syamsul Fatoni (The Constitutional Court of the Republic of Indonesia, 2020)
In connection with the submission of judicial review to the Constitutional Court conducted by the Indonesian Judges Association (IKAHI) and the Indonesian Prosecutors Association (IJI), this research aims to examine the criminalization of Judges and Prosecutors in the Criminal Justice System as regulated in Act Number 11 of 2012 about the Juvenile Criminal System. This type of research is descriptive normative juridical, namely inventorying the legislation through the statute approach and conceptual approach to develop legal arguments and legal opinions in solving legal issues. Whereas legal material collection techniques (primary, secondary and tertiary) use literature study and analysis with deductive thinking logic. The results showed that the submission of the judicial review submission by the Constitutional Court was appropriate because Law Number 11 of 2012 concerning the Child Criminal Justice System is a form of protection and enforcement of children’s rights in the criminal justice process so that criminalization efforts against officers and law enforcement officers, especially against Judges (Article 96, Article 100 and Article 101) and Prosecutors (Article 99) will influence the criminal justice system. In addition, the principles of criminalization must be considered, namely the principles of legality, the principle of subsidiarity and the principle of equality or equality so as to realize structural synchronization, substantial synchronization and cultural synchronization in the juvenile justice system.